Trends of Dengue Cases Reported at Tertiary Care Hospital of Metropolitan City of Maharashtra: A Record Based Study - Pol, Sujata S; Rajderkar, Shekhar S; Gokhe, Seema S Bansode (National Journal of Community Medicine, 2017)
Background & Objectives: Recent national data showed increasing trends of dengue prevalence but significant decrease in death rates.1Understanding trends and epidemiology of dengue outbreaks would help in effective control of dengue in city. Therefore, the research was planned to study & compare the trends of dengue cases reported at Tertiary hospital, state & district levels during 2009 to 2015. Methods: Six years data on ‘Dengue cases admitted in a tertiary care hospital’ was obtained from the Satellite Disease Surveillance Unit of Tertiary care hospital. District and state level data on dengue was mobilised from Public Health department authorities and websites. Tables and graphs were prepared. Data analysis and compilation was done with Microsoft Excel 2013. Result: A total of 56,981 patients with fever were screened for dengue at tertiary hospital during the study period. Of these, 5082 patients (8.91%) were tested positive. There was tenfold increase in the Dengue cases in six years. Rise of confirmed dengue cases was seen at District and state level. ‘Males’ and ‘Patients between 13-30 years age group’ were more affected. There was declining trend of dengue case fatality rate. Conclusion: Incresing trend of dengue indicates an alarming situation in the city and stressesmore preparedness during monsoon season.